Farmer Field Days and Demonstrator Selection for Increasing Technology Adoption - Emerick, Kyle; Dar, Manzoor H. (The Review of Economics and Statistics, 2021)
Inadequate learning is an oft-cited friction impeding the adoption of improved agricultural technology in the developing world. We provide experimental evidence that farmer field days, an approach used throughout the world where farmers meet, learn about new technology, and observe its performance, alleviate learning frictions and increase adoption of an improved seed by 40%. Further analysis demonstrates that these field days are both cost-effective and have a greater impact on poorer farmers. In contrast, we find no evidence that selecting the first adopters of new technology in participatory village meetings has any effect on future adoption.